EFFECTIVE 5D BIM REQUIREMENTS FOR RISK MITIGATION DURING PRE-CONTRACT STAGE - Nazirul Fariq; Syuhaida Ismail; Nur Izzati Ab Rani (Journal of Surveying, Construction and Property, 2022)
The implementation of building information modelling (BIM) can be challenging without proper processes, procedures and standards. As the development of BIM progresses, there are concerns related to the five-dimensional (5D) BIM procedures in producing deliverables from the cost aspects of the project that adopts BIM technology. While the concerns may expose to amount of risks that can influence the project cost, this paper is determined to investigate the technical risks of 5D BIM practice and explore risk mitigation strategies for the construction project that adopts 5D BIM technology. Three main groups of technical risks were identified and reviewed, namely modelling issues, poor execution procedures and design change issues. The population of this paper consists of quantity surveyors and the respondents come from consultancy firms, contractors and developers. This paper also found twelve critical issues and challenges of 5D BIM implementation that had been analysed with the relative importance index (RII) analysis. Risk mitigation strategies are proposed to make a positive impact on the 5D BIM implementation, which consist of regular checks and balances, improve skills and knowledge through training and acquire suitable 5D BIM applications. The use of a BIM execution plan (BEP) and BIM protocol are also being discussed in this paper.